The Latin-american obesity consensus (Brazilian Journal of Behavioral and Cognitive Therapy, 2001)
Obesity is an element of risk to several pathologies and its prevalence is increasing in many countries. It was considered a serious health problem by the World Health Organization and several kinds of treatment have been proposed to reduce body weight. There is a strong need to systematize the strategies applied in obesity treatment and its results. To this purpose, a Latin-American Obesity Consensus has been elaborated, as a document which describes the efficient and ethical strategies to be applied in such treatments. The aim of this article is describing the applied methodology in the elaboration of this Latin-American Obesity Consensus, its contents and the governamental policies that are being developed to reduce the prevalence of obesity.